Penerapan Posisi Semi-Fowler terhadap Saturasi Oksigen pada Pasien TB Paru di Ruangan Mawar RSUD Kabupaten Subang - Annisa Dwi Yunarni; M. Iqbal Angga Kusuma; Minanton Minanton (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease that attacks the respiratory system, especially the lungs, and can cause various clinical symptoms, one of which is decreased oxygen saturation (SpO₂). Decreased oxygen saturation can worsen the patient's condition and affect their quality of life. Therefore, effective interventions are needed to increase oxygen levels in the body, especially through safe and easy-to-implement non-pharmacological approaches. One intervention commonly used in nursing practice is the semi-Fowler position, which is a lying position with the head of the bed elevated around 30–45 degrees, which is believed to improve lung expansion and increase ventilation. This study aims to evaluate the effectiveness of implementing the semi-Fowler position on increasing oxygen saturation in pulmonary TB patients. The study was conducted using a descriptive method through a case study approach on three pulmonary TB patients treated in the Mawar Room of Subang District Hospital. Data were collected through direct observation of oxygen saturation using a pulse oximeter at minute 0 (before intervention), minute 10, minute 30, and more than minute 60 after the patient was placed in the semi-Fowler position. The results showed a significant increase in the SpO₂ values of the three patients after 30 minutes in the semi-Fowler position, with an average increase from 92–93% to 95–96%, and these values tended to be stable for more than 60 minutes after the intervention. These findings suggest that the semi-Fowler position can be an effective non-pharmacological nursing intervention option to increase oxygen saturation in pulmonary TB patients. The application of this position is recommended in daily nursing practice to help overcome respiratory disorders, increase comfort, and accelerate the recovery process of pulmonary TB patients.